The regulation of distributed solar power generation in Costa Rica: Status, challenges and options for the future - Jorge Cornick (Inter-American Development Bank (IDB), 2020)
This paper provides a general characterization of overall power regulation and a detailed characterization of the ongoing evolution of distributed rooftop photovoltaic (PV) regulation in Costa Rica. The paper further develops rooftop PV adoption models for several classes of consumers and evaluates maximum adoption rates under current regulations and alternative regulations, evaluating the impact on the cash flow of distribution utilities under each scenario. The paper subsequently assesses the institutional architecture of power regulation in Costa Rica and contrasts it with international best practices / regulatory consensus. Finally, the paper offers policy recommendations that might help Costa Rica achieve a better balance between conflicting regulatory goals through changes in regulatory rules and institutions.
Keywords: K23; K32; L94; L98; 330; Power regulation; Electricity; Solar energy